Excitation Function of the Al 27 (d,p) Al 28 Reaction between 2.2 and 12.6 MeV - Merlo Flores, Jorge (American Physical Society, 1962)
Fil: Merlo Flores, Jorge Comisión Nacional de Energía Atómica; Argentina